Long-term forage production of North American Shortgrass Steppe - Sala, O. E., author; Lauenroth, W. K., author; Ecological Society of America, publisher (Colorado State University. Libraries, 1992)
We evaluated the relationship between annual forage production and annual and seasonal precipitation and temperature at a shortgrass steppe site in north-central Colorado using a long-term data set (52 yr). We also constructed a relationship between forage production and aboveground net primary production (ANPP). Precipitation fluctuated randomly, but temperature had clear warming and cooling trends including a 17-yr warming trend from 1974 to 1990. Forage production was significantly related to both annual and seasonal precipitation but not temperature. Precipitation events between 15 and 30 mm accounted for most of the variability in production because they accounted for most of the variability in precipitation and because they wetted the soil layers that have the largest effect on production. Forage production amplified variability in annual precipitation. Production showed time lags of several years in responding to increases in precipitation. Change in vegetation structure has a characteristic response time, which contrains production responses in wet years. Constraint caused by vegetation structure is the reason why regional ANPP-precipitation models have a steeper slope than long-term models and point out a weakness of exchanging space for time in predicting production patterns.
Keywords: temporal variability; water use efficiency; shortgrass steppe; aboveground net primary production; population-ecosystem interactions; forage production; spatial variability